2012
DOI: 10.1200/jco.2011.38.7522
|View full text |Cite
|
Sign up to set email alerts
|

Bosutinib Versus Imatinib in Newly Diagnosed Chronic-Phase Chronic Myeloid Leukemia: Results From the BELA Trial

Abstract: A B S T R A C T PurposeBosutinib is an oral Src/Abl tyrosine kinase inhibitor. The phase III Bosutinib Efficacy and Safety in Newly Diagnosed Chronic Myeloid Leukemia (BELA) trial compared bosutinib with imatinib in newly diagnosed, chronic-phase chronic myeloid leukemia (CML). Patients and MethodsA total of 502 patients were randomly assigned 1:1 to bosutinib 500 mg per day or imatinib 400 mg per day. ResultsThe complete cytogenetic response (CCyR) rate at 12 months was not different for bosutinib (70%; 95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
385
2
15

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 415 publications
(418 citation statements)
references
References 25 publications
(14 reference statements)
16
385
2
15
Order By: Relevance
“…Although many patients with CML in chronic phase (CML-CP) achieve and maintain durable responses under imatinib, some need to be switched to alternative tyrosine kinase inhibitors (TKIs) due to intolerance and/or failure. After being first tested successfully in imatinib-resistant/-intolerant patients, second-generation TKIs (2GTKIs) (nilotinib, dasatinib, and bosutinib) were then utilized in the upfront setting and they were compared with imatinib among patients with CML-CP in three phase III prospective, randomized, companysponsored trials [1][2][3]. Although bosutinib was proven to be efficient among imatinib-resistant or -intolerant cases, it failed to demonstrate superior outcomes over imatinib in the BELA (Bosutinib Efficacy and Safety in Newly Diagnosed CML) trial, in which the primary end point was complete cytogenetic response (CCyR) at 12 months [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many patients with CML in chronic phase (CML-CP) achieve and maintain durable responses under imatinib, some need to be switched to alternative tyrosine kinase inhibitors (TKIs) due to intolerance and/or failure. After being first tested successfully in imatinib-resistant/-intolerant patients, second-generation TKIs (2GTKIs) (nilotinib, dasatinib, and bosutinib) were then utilized in the upfront setting and they were compared with imatinib among patients with CML-CP in three phase III prospective, randomized, companysponsored trials [1][2][3]. Although bosutinib was proven to be efficient among imatinib-resistant or -intolerant cases, it failed to demonstrate superior outcomes over imatinib in the BELA (Bosutinib Efficacy and Safety in Newly Diagnosed CML) trial, in which the primary end point was complete cytogenetic response (CCyR) at 12 months [3].…”
Section: Introductionmentioning
confidence: 99%
“…After being first tested successfully in imatinib-resistant/-intolerant patients, second-generation TKIs (2GTKIs) (nilotinib, dasatinib, and bosutinib) were then utilized in the upfront setting and they were compared with imatinib among patients with CML-CP in three phase III prospective, randomized, companysponsored trials [1][2][3]. Although bosutinib was proven to be efficient among imatinib-resistant or -intolerant cases, it failed to demonstrate superior outcomes over imatinib in the BELA (Bosutinib Efficacy and Safety in Newly Diagnosed CML) trial, in which the primary end point was complete cytogenetic response (CCyR) at 12 months [3]. Although the rate of major molecular response (MMR) in the bosutinib arm was significantly superior than that of patients receiving imatinib (41% vs. 27%, p < 0.001) as a secondary end point, the primary end point was not different for bosutinib (70%) versus imatinib (68%) (p = 0.601); consequently, bosutinib was not approved as a frontline treatment option for patients with CML-CP since the primary end point was not met [3].…”
Section: Introductionmentioning
confidence: 99%
“…8 The results of bosutinib treatment, second-line and first-line, are similar to those of nilotinib and dasatinib, although the differences in comparison with imatinib are less significant, because of the side effect of the drug, mainly diarrhea and increase of aspartate and alanine aminotransferase.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 77%
“…8 A fifth compound (Ponatinib, Ariad) has been tested in second-line and third-line treatment. 9 Imatinib, first of the class, was introduced more than 10 years ago.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…At a median follow-up of 30-35 months, MCyR and CCyR was achieved by 59% and 48%, respectively, of patients with chronic phase disease [19]. Bosutinib has also been investigated as a first-line therapy in the phase III BELA trial, with the CCyR rate found to be no different to that of imatinib at 12 months, although superiority of bosutinib in some secondary efficacy endpoints was evident [70,71]. This same study provided the ideal framework to evaluate the safety of bosutinib as it was administered in a controlled way (i.e., vs. imatinib) in over 500 patients followed for a minimum of 5 years.…”
Section: Bosutinibmentioning
confidence: 99%